Abstract ID: 35 Monte Carlo dosimetric study for preclinical small animal hadrontherapy using Geant4 toolkit. (October 2017) - Pisciotta, Pietro; Russo, Giorgio; Pablo Cirrone, Giuseppe Antonio; Romano, Francesco; Cammarata, Francesco Paolo; Petringa, Giada; Forte, Giusi Irma; Lamia, Debora; Acquaviva, Rosaria; Gilardi, Maria Carla; Cuttone, Giacomo
Abstract : Preclinical studies represent an important step to study molecular mechanism induced inside cells in response to ionizing radiations. The scope was the study of the preliminary steps to perform particle treatment of cancer cells inoculated in small animals and to realize a preclinical hadrontherapy facility. At this scope, a well-defined dosimetric protocol was developed to perform the steps needed in order to perform a precise proton irradiation in small animals and achieve highly conformal dose. Homemade positioning system for small animals was developed at INFN-LNS(Italy) and an accurate Monte Carlo simulation was developed. The application, developed using Geant4.10.03 version, includes in the current version of the advanced example "Hadrontherapy"[1] the main functionalities of the "DICOM" extended example[2] . In this way, this application simulates the CATANA beam line geometry and includes the capability to implement DICOM-TC images as target. The application will be used to carry out dosimetric and LET studies[3] using the real target composition. This application was validated comparing its results with experimental measurements. A validation test, using solid water slabs phantom, and a treatment simulation, irradiating a PMMA phantom that simulate subcutaneous tumours, were executed at CATANA facility using in both cases EBT3-Gafchromic films as dose detector. The dosimetric results were compared with the simulation ones using Kolmogorov and gamma index test. Experimental data are in good agreement with the simulation ones. The phantom targets were included in the simulation environment using DICOM-TC images. Dosimetric measurements were useful to determine the efficiency of the developed Geant4 application and to demonstrate that it is a valid instrument to study the dose distribution in different types of phantoms with different kinds of geometry. This work has been carried-out in the perspective of realization of a preclinical hadrontherapy facility at INFN-LNS in order to implement interesting future in vivo studies using small animals.